A Textual analysis tracing the development of sensitive sex and gender issues in Batibot - Ayalin, Adrian M.
In recent years, Batibot got much attention when it aired episodes that dealt with matters such as pedophilia and sexual harassment. Sensing this, I have come up with a textual analysis of Batibot tracing how sensitive issues on sex and gender evolved within the program. Sampling of the shows analyzed was purposive. I textually analyzed three segments of the show per year using the scripts and videos available at the Batibot library. But then, being objective in this study, I have also included interviews with two child psychologists. I should say it is very necessary that I have a second opinion from the ones society value as knowledgeable in child care. With this textual analysis, I have carefully determined that Batibot broke the conservative culture of Philippine children's television -- by introdusing the radical, but unquestionably relevant issues of sex and gender in its shows.